One-pot colorimetric detection of molecules based on proximity proteolysis reaction - Park, Hyeon Ji; Kim, Yuseon; Yoo, Tae Hyeon (Biosensors and Bioelectronics, 2021)
Various types of molecules serve as biomarkers of diseases, and numerous methods have been reported to detect and quantify them. Recently, research efforts have been made to develop point-of-care (POC) tests, which contribute to early diagnoses of diseases, particularly in resource-limited settings. An assay performed in a homogeneous phase is an obvious route to develop these methods. Here, simple homogeneous methods based on proximity proteolysis reactions (PPR) are reported to detect biological molecules. A typical PPR system has been designed such that the proteolysis reaction between protease and zymogen is enhanced in the presence of a target analyte. The activated zymogen generates a color signal by hydrolyzing a chromophore. A protease and zymogen are linked to target binders using specific hybridization between complementary single-stranded DNAs, and several molecules, including proteins, antibodies, aptamers, and small molecules, are used as target binders. The developed assay methods successfully detected several kinds of analytes at subnanomolar concentrations with the one-step procedure and color signal. The modular design of the PPR-based assay will enable the development of simple POC diagnostics for various biomarkers.
Keywords: Biosensing; Color signals; Colorimetric detection; Early diagnosis; Homogeneous assays; One pot; Point of care; Proximity; Research efforts; Simple++; Biosensing Techniques; Colorimetry; DNA, Single-Stranded; Nucleic Acid Hybridization; Proteolysis; Biosensing; Colorimetric; Homogeneous assay; Proteolysis; Proximity